Verbal Communication in the Upin and Ipin Animated Series (Quantitative Content Analysis of Episode of the Upin and Ipin Series ÔÇô Gong Xi Fa Cai) - Yusra, Misrini; Arkaan, Deni; Unel, Temy; Okditazeini, Vannyora (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research will discuss verbal communication in the Upin and Ipin animation series, content analysis of episodes of the Upin and Ipin animation series ÔÇô Gong Xi Fa cai. This episode was chosen because it has the highest viewership in terms of the regional language. The research uses a quantitative research method that will discuss six aspects of verbal communication. The data collection technique in this study uses initial observations on the series, tracing the episodes with the highest viewing Malay category, encoding each visual scene of the episode and inferring the results of the episode on verbal communication. So it can be concluded that in the episode of the animated series Upin and Ipin ÔÇô Gong Xi Fa Cai has a score in the vocabulary aspect of 71%, racing 96%. voice intonation 93%, humor 8%, concise and clear 98% and timing 89%. Of the six aspects of verbal communication, the short and clear aspects part that received the highest score of 98% and it can be said that the characters tend to be more consistent with the core message of the conversation discussed when dialogue or communication.